2019
DOI: 10.1074/jbc.ra118.004469
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of peptide ligands targeting a specific ubiquitin-like domain–binding site in the deubiquitinase USP11

Abstract: Ubiquitin-specific proteases (USPs) reverse ubiquitination and regulate virtually all cellular processes. Defined noncatalytic domains in USP4 and USP15 are known to interact with E3 ligases and substrate recruitment factors. No such interactions have been reported for these domains in the paralog USP11, a key regulator of DNA double-strand break repair by homologous recombination. We hypothesized that USP11 domains adjacent to its protease domain harbor unique peptide-binding sites. Here, using a next-generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…One way to obtain selective inhibitors would be to target the non-catalytic regions rather than catalytic pockets. For instance, USP7 contains a central binding cleft in the N-terminal TRAF-like domain that is specifically recognized by [PA]-xx-S amino acid motifs found in p53, Hdm2, and Epstein-Barr nuclear antigen 1 [91]; the rhodanese domain of USP8 includes a ligase recognition site [124]; a non-catalytic ubiquitin-like (UBL) region of USP11 has been shown to interact with a helical motif but this site is absent from paralogs USP4 and USP15 [125]. However, current knowledge of such binding sites is still lacking for most DUBs and E3 ligases.…”
Section: Exploiting E3 Ligase and Dub Structural Diversitymentioning
confidence: 99%
“…One way to obtain selective inhibitors would be to target the non-catalytic regions rather than catalytic pockets. For instance, USP7 contains a central binding cleft in the N-terminal TRAF-like domain that is specifically recognized by [PA]-xx-S amino acid motifs found in p53, Hdm2, and Epstein-Barr nuclear antigen 1 [91]; the rhodanese domain of USP8 includes a ligase recognition site [124]; a non-catalytic ubiquitin-like (UBL) region of USP11 has been shown to interact with a helical motif but this site is absent from paralogs USP4 and USP15 [125]. However, current knowledge of such binding sites is still lacking for most DUBs and E3 ligases.…”
Section: Exploiting E3 Ligase and Dub Structural Diversitymentioning
confidence: 99%
“…Using a ubiquitin chain cleavage assay, Harper and colleagues reported that USP11 may cleave a panel of Lys (48, 63, 6, 33, and others)-linked linear ubiquitin chains, indicating that USP11 may function in regulating protein activity (51). Recently, Dreveny and her group reported the identification of peptide ligands that exclusively targeted the UBL domain of USP11 without affecting its functional paralogs USP4 and USP15, providing an ideal platform to next-generation biochemical tools for limiting USP11 activity (52). Thus, there are exciting opportunities to specifically target USP11 with minimal off-target impact.…”
Section: Usp11mentioning
confidence: 99%
“…Spiliotopoulos et al (5) next analyzed two prototype peptides for USP11 binding and function. In vitro, the peptides bound USP11 with an equilibrium dissociation constant (K D ) of ϳ10 M, and were specific, unable to bind the USP4 and USP15 paralogs.…”
Section: Inhibiting Deubiquitinase (Dub) Function Is a Promising Stramentioning
confidence: 99%